Intracellular protozoan parasites: living probes of the host cell surface molecular repertoire. (December 2019) - Pavlou, Georgios; Milon, Geneviève; Tardieux, Isabelle
Highlights: The composite and dynamic metazoan cell surface are probed by protozoan parasites. Invading protozoans breach target membranes to escape from unfavourable situations. Invading protozoans wound and trigger membrane repair process in hosting cells. Protozoans design invasive multi-function nanodevices that target the cell surface. Need for more biomechanics studies to decode how protozoans re-sculpt cell surface. Abstract : Intracellular protozoans co-evolved with their mammalian host cells a range of strategies to cope with the composite and dynamic cell surface features they encounter during migration and infection. Therefore, these single-celled eukaryotic parasites represent a fascinating source of living probes for precisely capturing the dynamic coupling between the membrane and contractile cortex components of the cell surface. Such biomechanical changes drive a constant re-sculpting of the host cell surface, enabling rapid adjustments that contribute to cellular homeostasis. As emphasized in this review, through the design of specific molecular devices and stratagems to interfere with the biomechanics of the mammalian cell surface these parasitic microbes escape from dangerous or unfavourable microenvironments by breaching host cell membranes, directing the membrane repair machinery to wounded membrane areas, or minimizing membrane assault using discretion and speed when invading host cells for sustained residence.